2019
DOI: 10.1152/ajpregu.00157.2019
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual differences in the ischemic stimulus and other technical considerations when assessing reactive hyperemia

Abstract: Reactive hyperemia is an established, noninvasive technique to assess microvascular function and a powerful predictor of all-cause and cardiovascular morbidity and mortality. Emerging evidence from our laboratory suggests a close link between reactive hyperemia and the metabolic rate of the ischemic limb and the existence of large interindividual differences contributing to markedly different stimuli to vasodilate. Here we relate forearm tissue desaturation (i.e., the ischemic stimulus to vasodilate, measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…The inclusion of a broad age range and not accounting for physical activity or fitness levels may have also contributed to variance in our data (Black, Green, & Cable, 2008); however, this may also strengthen the generalizability of our findings. Furthermore, the direct relationship between occlusion duration and the magnitude of post-occlusion CEUS measurements in the current study is consistent with findings from other hyperaemic response studies using plethysmography (Bauer, Bruegger, Gamble, & Christ, 2002) and NIRS (Iannetta et al, 2019;McLay et al, 2016;Rosenberry et al, 2018;Rosenberry, Trojacek, Chung, Cipher, & Nelson, 2019).…”
Section: Limitationssupporting
confidence: 91%
“…The inclusion of a broad age range and not accounting for physical activity or fitness levels may have also contributed to variance in our data (Black, Green, & Cable, 2008); however, this may also strengthen the generalizability of our findings. Furthermore, the direct relationship between occlusion duration and the magnitude of post-occlusion CEUS measurements in the current study is consistent with findings from other hyperaemic response studies using plethysmography (Bauer, Bruegger, Gamble, & Christ, 2002) and NIRS (Iannetta et al, 2019;McLay et al, 2016;Rosenberry et al, 2018;Rosenberry, Trojacek, Chung, Cipher, & Nelson, 2019).…”
Section: Limitationssupporting
confidence: 91%
“… 13 , 18 Our findings demonstrated that only StO 2slope _ 10s was significantly slower in older adults with CVD risk factors compared to healthy older adults and to healthy young individuals, suggesting that StO 2slope_10s may be a more sensitive NIRS parameter for assessing reactive hyperemia. The StO 2slope _ 10s has typically been adopted to assess O 2 resaturation rate, since previous studies have reported that this parameter is correlated with reactive hyperemia measured in the brachial artery 20 and with FMD response. 8 , 11 It has been postulated that the StO 2slope _ 10s may be a stimulus for FMD response given that FMD is evoked by increasing blood flow after cuff release.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria for older adults at high risk for CVD were age ≥ 60 years and possessing at least four CVD risk factors, according to a previous study demonstrating that presence of three or more CVD risk factors is related to microvascular dysfunction. 10 , 20 The following CVD risk factors were used as inclusion criteria: triglycerides ≥ 150 mg/dL; total-cholesterol ≥ 200 mg/dL; LDL-cholesterol ≥ 150 mg/dL, HDL-cholesterol ≤ 40 mg/dL for men and ≤ 50 mg/dL for women; high-blood glucose ≥ 120 mg/dL and/or taking oral hypoglycemic medications; and high systolic blood pressure (SBP) ≥ 135 mm Hg, and/or high diastolic blood pressure (DBP) ≥ 90 mm Hg, and/or taking anti-hypertensive medications. The exclusion criteria included human immunodeficiency virus (HIV); cancer; rheumatoid arthritis; smoking; and chronic obstructive pulmonary disease; as well as participants not being engaged in any exercise program.…”
Section: Methodsmentioning
confidence: 99%
“…While reduced NO scavenging by haemoglobin is a very plausible explanation, as put forth by the investigators, it is interesting to consider the role of reduced arterial oxygen content (and oxygen delivery) on the present results. Indeed, our laboratory has recently highlighted the importance of the 'ischaemic stimulus' on reactive hyperaemia (Rosenberry et al 2019). While the between condition difference in peak reactive hyperaemia did not reach statistical significance, there was a clear trend favouring the Journal Club J Physiol 598.24 haemodilution condition.…”
Section: Implications Of Results and Future Directionsmentioning
confidence: 94%
“…Indeed, our laboratory has recently highlighted the importance of the ‘ischaemic stimulus’ on reactive hyperaemia (Rosenberry et al . 2019). While the between condition difference in peak reactive hyperaemia did not reach statistical significance, there was a clear trend favouring the haemodilution condition.…”
Section: Introductionmentioning
confidence: 99%